Proceedings of the 22nd International Conference on Industrial Engineering and Engineering Management 2015 : Innovation and Practice in Industrial Engineering and Management.: Innovation and Practice in Industrial Engineering and Management. (Volume 2) (2016) - Unknown
No abstract available